Evaluation of Ground Water Potential in Ekpri-Ikang, Bakassi Local Government Area, Cross River State, Nigeria. â€œA Case Study of Open Bible Standard Church Premisesâ€ - Umoren, Emmanuel; Agbasi, Okechukwu; Emmanuel, Eniang (International Journal of Advanced Geosciences, 2017)
Electrical resistivity survey using Schlumberger Vertical Electrical Sounding (VES) field technique was carried out at Ekpri Ikang in Bakassi local government area of Cross River State. The survey is aimed at determining the water bearing formation of the area. Data acquired were interpreted using WinRes Program into a curve showing true resistivity and thickness of the subsurface layers. Result indicates that there are four distinct layers in the study area. Analyses of the data and interpretation of the sounding curve reveals that the water bearing layer exist in the layer two (2) and three (3) with resistivity values of 347.6â„¦ and 375.5â„¦, also with thickness of 14.5m and 21.3m, depth of 39.6m and 61.0m. It is therefore recommended that boreholes for good drinking water be drilled to the layer two (2) and three (3) of the investigated area.